Analysis of Human Resources and Information Technology (IT Governance) with COBIT 5 - Rima Tamara Aldisa (IJISTECH (International Journal of Information System and Technology), 2022)
Technology is currently developing rapidly and plays a very important role in various sectors of human life, especially information technology in the field of human resources. With the development of this technology, benefits can be felt, namely the efficiency and effectiveness of activities that are still difficult to do manually. The application of information technology has high perceived investment and benefits so there is a need for significant Information Technology management. The use of information technology by institutions has been carried out for a long time, with increasing intensity. The human resources that currently exist in the company are not in accordance with the competence, reliability and educational background that are in accordance with the job, so a step is taken in managing human resources with appropriate information technology.